POSTOPERATIVE AND CANCER PAIN NEED PROPER ANALGESIA - Nikolay Yanev; Mila Vlaskovska (Peytchinski Publishing, 2016)
The authors surveyed the clinical data and reviewed the literature on the management of post-operative and cancer pain. The conclusion was made that pain management during post-operative period or in status of advanced cancer necessitates effective pharmacotherapy with non-opioid and opioid analgesics. Data for pharmacokinetics and pharmacodynamics of widely used analgesic drugs are listed. The authors provide practical guidelines for the management of post-operative and cancer pain in clinical wards as well as in outpatients departments.